2016
DOI: 10.1002/app.43670
|View full text |Cite
|
Sign up to set email alerts
|

Influence of support layer and PDMS coating conditions on composite membrane performance for ethanol/water separation by pervaporation

Abstract: A systematic study was performed on the combination of support properties and polydimethylsiloxane (PDMS) coating conditions for the lab-scale preparation of a defect-free, thin film composite membrane for organophilic pervaporation. Support layers having comparable surface porosities were prepared from three polymers with different chemical composition (PVDF, PSF, PI). Their exact role on the deposition of the PDMS coating (i.e., wetting and intrusion) and the final membrane performance (i.e., effect on mass … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(26 citation statements)
references
References 50 publications
2
24
0
Order By: Relevance
“…Despite the generally accepted opinion that the porous substrate of supported membranes does not significantly affect the mass transfer of low-molecular-weight components in pervaporation, the substrate polymer type, as well as substrate porosity, can have a significant effect on the transport properties of the supported membrane [46][47][48]. In this section, to understand the mechanism of mass transfer in pervaporation, the characteristics of commercial porous substrates PAN and UPM-20 were studied by SEM, AFM, the standard porosimetry method, contact-angle measurements, and ultrafiltration experiments.…”
Section: Influence Of the Substrate On The Mass Transportmentioning
confidence: 95%
See 2 more Smart Citations
“…Despite the generally accepted opinion that the porous substrate of supported membranes does not significantly affect the mass transfer of low-molecular-weight components in pervaporation, the substrate polymer type, as well as substrate porosity, can have a significant effect on the transport properties of the supported membrane [46][47][48]. In this section, to understand the mechanism of mass transfer in pervaporation, the characteristics of commercial porous substrates PAN and UPM-20 were studied by SEM, AFM, the standard porosimetry method, contact-angle measurements, and ultrafiltration experiments.…”
Section: Influence Of the Substrate On The Mass Transportmentioning
confidence: 95%
“…Thus, based on the obtained pervaporation data on the separation of the isopropanol-water mixture and data on the characterization of commercial porous substrates, it can be concluded that a supported membrane with a thin selective layer based on PVA-PAH deposited on porous PAN substrate and modified with 10 PEL bilayers via LbL deposition (PVA-PAH/LbL-10 PAN membrane) has the best selective properties with respect to water. On the other hand, the UPM-20 substrate, characterized by a much higher porosity, did not limit the mass transport of the low-molecular-weight component, which logically favored a higher permeance [46]. Nevertheless, at the same time, the water selectivity was reduced due to the coupling effect of several parameters: a more open pore structure, a rougher and more hydrophobic surface, and facilitated diffusion of iPrOH in UPM-20 (compared to PAN).…”
Section: Pan Upm-20mentioning
confidence: 97%
See 1 more Smart Citation
“…Although the morphology and chemical nature of the selective layer mainly control the membrane performance, according to many studies in this field, the pore size, pore length, porosity, hydrophilicity, and reactivity of the sublayer might influence the final properties of the prepared membranes. Some studies have proved the significant effects of the sublayer on pervaporation. While the sublayer should preserve the mechanical stability of the membrane, the selective layer is responsible for high flux and selectivity .…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have proved the significant effects of the sublayer on pervaporation. While the sublayer should preserve the mechanical stability of the membrane, the selective layer is responsible for high flux and selectivity . Hence, the development of a porous support with high mechanical and chemical stability, proper porosity, and flexibility is required.…”
Section: Introductionmentioning
confidence: 99%